Structural-phase transformations and evolution of defect structure under thermal influence and hydrogenation of Cr-coated E110 zirconium alloy: Experimental research and first-principal calculations; Materials Chemistry and Physics; Vol. 335 - Kudiyarov V. N. Victor Nikolaevich; Kruglyakov M. A. Mark Aleksandrovich; Lomygin A. D. Anton Dmitrievich; Laptev R. S. Roman Sergeevich; Ushakov I. A. Ivan Alekseevich; Svyatkin L. A. Leonid Aleksandrovich; Vrublevsky D. B. Dmitry Borisovich (2025, 2025)
Title screen